Surgical Residents´ Results Seem to be Non-Inferior Comparing to More Experienced Surgeons in Femoral Neck Fracture Osteosynthesis - Forsbacka Nora; Kolari Terhi; Talme Marjo; Bister Ville (Springer, 2025)
Purpose of the Study Femoral neck fracture osteosynthesis is usually performed by using dynamic hip screw (DHS) or multiple parallel cannulated screws (MCS). In orthopedic surgery training, certain hip fractures are one of the most common operations performed by residents. It has been questioned, whether residents can provide as safe treatment and patient outcomes as those of more experienced surgeons. The aim of this study was to evaluate the efect of surgical experience on risk of complications by comparing the surgical performance and clinical outcomes in femoral neck osteosyntheses between surgical residents and orthopaedic surgeons.
Methods All patients with femoral neck fracture admitted to Helsinki and Uusimaa Hospital District (HUS) Hyvinkää Hospital from 2011 to 2016 were collected as research material. 88 hip fractures (87 patients) treated with DHS or MCS osteosyntheses were included in this study. The patients were divided into 2 groups, based on the surgeon’s experience: an orthopedic surgeon group (n=68) and a surgical resident group (n=20). All data from complications, reoperations, and the duration of operations were collected.
Results There was no signifcant diference in characteristics of operated patients between orthopaedics and residents group. There was no signifcant diference in complications or re-operations between groups (p=0.4, p=0.2). Surgical residents had statistically longer surgical time (mean 76 min, 95% CI 62.92 min, mean 46 min, 95% Cl 42.51 min; p-value<0.001). Still surgical time was not a risk factor for complication (p-value 0.5).
Conclusion Our results show that surgical residents´ outcomes in femoral neck fracture osteosynthesis seem to be as favorable as those of orthopedic surgeons; the operations just last slightly longer.